PELUANG DAN TANTANGAN PELAKSANAAN PATEN ESENSIAL STANDARD (STANDARD ESSENTIAL PATENT/SEP) DI INDONESIA - Rani Nuradi (Jurnal De Lege Ferenda Trisakti, 2023)
Standards are technical requirements or something that is standardized, including procedures and methods that are formulated based on the consensus of all parties, the government, and international decisions related to safety, security, health, environmental conditions, advancements in science and technology, experience, as well as current and future developments to achieve maximum benefits. In the current development of technology and global economic competition, patented technologies often serve as standards (Standard Essential Patent, or SEP). The implementation of SEP itself is possible as long as the patent holder agrees and adheres to the principles of fair, reasonable, and non-discriminatory terms, also known as FRAND (Fair, Reasonable, and Non-Discriminatory) principles. When the FRAND principles are not followed, for example, when the patent holder is unwilling to provide a license or sets the licensing fee too high, issues may arise. This paper discusses examples of SEP implementation in Indonesia through two case studies, aiming to provide insights for policymakers, particularly the Directorate General of Intellectual Property and the National Standardization Agency, to take appropriate steps in maintaining a balance between the rights and obligations of patent holders and the public